2016
DOI: 10.1542/peds.2015-2851k
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Treatment of Severe Irritability and Problem Behaviors in Autism: A Systematic Review and Meta-analysis

Abstract: BACKGROUND: Autism spectrum disorder (ASD) is increasingly recognized as a public health issue. Irritability and aggression (IA) often negatively affect the lives of people with ASD and their families. Although many medications have been tested for IA in ASDs in randomized controlled trials (RCTs), critical quantitative analyses of these trials are lacking in the literature. OBJECTIVES:To systematically review and quantitatively analyze the efficacy and safety of pharmacologic treatments for IA in youth with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 195 publications
(137 citation statements)
references
References 63 publications
4
124
0
7
Order By: Relevance
“…6 Importantly, I/PB can jeopardize educational and recreational placements and even lead to inpatient psychiatric hospitalization 7 or residential placement. 8 As presented by Fung and colleagues 9 in this issue, meta-analysis of controlled trials confirms the efficacy of 2 atypical neuroleptics, risperidone and aripiprazole, approved by the US Food and Drug Administration for the management of "severe irritability" based on clinical trials in children with ASD who have frequent I/PB that is interfering with development, functioning, or relationships. Atypical neuroleptics have become widely used in patients with ASD 10 but carry a significant risk of metabolic 11 and neurologic adverse events.…”
Section: S137 Pediatrics Volume 137 Number S2 February 2016mentioning
confidence: 85%
See 1 more Smart Citation
“…6 Importantly, I/PB can jeopardize educational and recreational placements and even lead to inpatient psychiatric hospitalization 7 or residential placement. 8 As presented by Fung and colleagues 9 in this issue, meta-analysis of controlled trials confirms the efficacy of 2 atypical neuroleptics, risperidone and aripiprazole, approved by the US Food and Drug Administration for the management of "severe irritability" based on clinical trials in children with ASD who have frequent I/PB that is interfering with development, functioning, or relationships. Atypical neuroleptics have become widely used in patients with ASD 10 but carry a significant risk of metabolic 11 and neurologic adverse events.…”
Section: S137 Pediatrics Volume 137 Number S2 February 2016mentioning
confidence: 85%
“…Atypical neuroleptics have become widely used in patients with ASD 10 but carry a significant risk of metabolic 11 and neurologic adverse events. 9,12 These concerns mandate consideration of lower-risk interventions, even for severe I/PB, targeting other factors, such as medical problems or communication challenges that have been identified as potentially contributory to I/PB in the individual patient.…”
Section: S137 Pediatrics Volume 137 Number S2 February 2016mentioning
confidence: 99%
“…Pharmacologic treatment of severe irritability and problem behaviours in autism: A systematic review and metaanalysis (5) Autism spectrum disorder (ASD) is increasingly recognised as a public health issue. Irritability and aggression (IA) often negatively affect the lives of people with ASD and their families.…”
Section: Ariyasinghe Ss Williamsmentioning
confidence: 99%
“…For many such trials the compounds tested showed little or no measureable efficacy relative to controls [1,21]. Some compounds where double-blind trials did show statistically significant efficacy relative to control are: n-acetylcysteine where Hardan et al, found irritability decreased based on the Aberrant Behavioral Checklist (ABC) irritability subscale [22]; sulforaphane where Singh et al, found behavior improved based on an ABC and Social Responsiveness Scale measures [23]; l-carnitine where Fahmy et al, found behavior improved based on a Childhood Autism Rating Scale [24]; and a multivitamin that contained substantial amounts of methyl-sufonyl-methane and n-acetyl cysteine where Adams et al, found behavior improved based on a Parental Global Impressions measure [25].…”
Section: Sulfur Containing Antioxidants As Therapeutics For Autismmentioning
confidence: 99%
“…With the exception of some antipsychotics which have significant side effects, there are few pharmaceuticals which have shown efficacy as treatments for the debilitating symptoms commonly associated with autism [1]. While autism is traditionally defined behaviorally, the literature suggests that many with autism have some similarities of biochemistry [2,3].…”
Section: Introductionmentioning
confidence: 99%